A novel boiler cold-end optimisation system based on bypass flue in coal-fired power plants: Heat recovery from wet flue gas. (1st June 2018) - Yan, Min; Zhang, Liang; Shi, Yuetao; Zhang, Liqiang; Li, Yuzhong; Ma, Chunyuan
Abstract: Recovering waste heat from the flue gas of coal-fired power plants and utilizing it reasonably is an effective way to increase power plant efﬁciency. The bypass ﬂue process is an improved boiler cold-end optimisation process and has greater energy savings than the traditional low-temperature economizer process. To achieve better stepwise utilization of flue gas, a novel boiler cold-end optimisation system based on bypass flue was proposed in this study. In the proposed process, flue gas waste heat after the wet ﬂue gas desulphurizer was recovered and used as the first-stage heat source to preheat the ambient air, resulting in less heat transfer in the air preheater and more ﬂue gas flowing into the bypass ﬂue. The thermodynamic and techno-economic performance of the novel process were calculated and compared with the bypass flue process, using data from a typical 1000 MW coal-fired power plant. The thermal economy results show that the net standard coal consumption rate of the proposed process could decrease by 5.38 g/(kW·h) compared with the original unit, a 1.76 g/(kW·h) greater reduction than the 3.62 g/(kW·h) of the bypass ﬂue process. The techno-economic analysis results show that the net present value of the 15 years lifespan is 21.61 million USD compared with the original unit, and is 5.13 million USD more than the 16.48 million USD of the bypass ﬂue process. Highlights: A novel method for recovering flue gas waste heat after WFGD is proposed. The recovered waste heat is integrated properly to preheat the air. Higher thermal efﬁciency is achieved in the proposed process. Greater economic beneﬁts are achieved in the proposed process.